PREVENTION OF ILLEGAL FUEL SMUGGLE IN THE BORDER OF EAST NUSA TENGGARA AND TIMOR LESTE - Sumbi, Evelyn Bellatrix (Faculty of Law, Khairun University, 2021)
Indonesia is one of the countries with abundant natural resources, this can be seen from the abundant human resources that are able to improve the management of existing natural resources. This is also emphasized in Article 33 paragraph 3 of the 1945 Constitution of the Republic of Indonesia (UUD RI 1945). A different fact is faced by small communities in the border area between Nusa Tenggara Timur Indonesia and Timor Leste. The problem is that the small communities there are not unable to enjoy subsidy relief due to wrong targets but because of smuggling carried out to neighboring countries. In several criminal cases that occurred in the border area between East Nusa Tenggara and Timor Leste, one of them was the Indonesian National Armed Forces (Satgas Pamtas) RI-RDTL East Sector Border Security Task Force, Yonif Raider 408 / Sbh, thwarted the smuggling of thousands of liters of fuel oil. (BBM) in the RI-RDTL border area.There have been many efforts made by the government to improve the welfare of its citizens by utilizing existing natural resources, especially in the oil and gas sector, one of which is in terms of access to energy consumption through fuel oil (BBM) subsidies which are still being debated. Some are of the view that state assistance must be maintained, but on the other hand, they still think that fuel subsidies are still not on target. A different fact is faced by small communities in the border area between Nusa Tenggara Timur Indonesia and Timor Leste. In addition, at the opening of the International Convention on Indonesian Upstream Oil and Gas 2020, which was organized by SKK Migas, the Government also supported the improvement of the investment climate in Indonesia's upstream oil and natural gas (oil and gas) sector, amid a decline in national oil and gas production and sluggish movement of strategic industries due to the the Covid-19 pandemi.